DATA MINING KLASTERISASI PENJUALAN ALAT-ALAT BANGUNAN MENGGUNAKAN METODE K-MEANS (STUDI KASUS DI TOKO ADI BANGUNAN) - M. Hasyim Siregar (Universitas Islam Kuantan Singingi, 2018)
In the world of business competition today, we are required to continually develop business to always survive in the competition. To achieve this there are a few things that can be done is to improve the quality of the product, adding the type of product and operational cost reduction company with how to use data analysis of the company. Data mining is a technology that automate the process to find interesting patterns and sensitive from the large data sets. This allows human understanding about finding patterns and scalability techniques. The store Adi Bangunan is a shop which is engaged in the sale of building materials and household who have such a system on supermarket namely buyers took own goods that will be purchased. Sales data, purchase goods or reimbursed some unexpected is not well ordered, so that the data is only function as archive for the store and cannot be used for the development of marketing strategy. In this research, data mining applied using the model of the process of K-Means that provides a standard process for the use of data mining in various areas used in the classification of because the results of this method can be easily understood and interpreted.